2020
DOI: 10.3892/ol.2020.11910
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of microRNA‑21, PTEN and p27 in cancer tissues of patients with non‑small cell lung cancer

Abstract: Expression and clinical significance of micro-RNA-21, PTEN and p27 in cancer tissue of patients with non-small cell lung cancer (NSCLC) were investigated. In this study, cancer tissue and adjacent tissue specimens from 230 patients with NSCLC were collected from thoracic surgery department in Hubei Cancer Hospital from March 2010 to February 2016. The expression of miRNA-21, PTEN and p27 in cancer tissue and adjacent tissue of patients with NSCLC was detected by RT-PCR. Combined with clinical information, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…A total of 1603 participants from 15 studies [ 22 , 50–72 ] were included in our meta-analysis of prognosis. Among these studies, 12 provided data on OS of lung cancer patients [ 60 , 62–72 ], 1 on PFS [ 61 ], 1 on DFS [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 1603 participants from 15 studies [ 22 , 50–72 ] were included in our meta-analysis of prognosis. Among these studies, 12 provided data on OS of lung cancer patients [ 60 , 62–72 ], 1 on PFS [ 61 ], 1 on DFS [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the cohort was too small to make definitive statements [ 101 ]. Similarly, there was a certain correlation between smoking, TNM staging, lymph node metastasis, differentiation and miRNA-21, PTEN and p27 expression [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Protein p27 expression seems to be associated with a better prognosis [ 45 ]. In a systematic review, Zhuang et al [ 46 ] reported that in NSCLC patients, a high p27 expression was associated with better survival. This data may be interesting if integrated with those reported in the previous section.…”
Section: Effects Of Statins On Lung Cancer Molecular Pathwaysmentioning
confidence: 99%
“…A previous study proved that low P 27 expression developed metastasis and predicted a poorer prognosis of eyelid sebaceous gland carcinoma [11]. To our knowledge, low P 27 levels have also been associated with poor survival outcomes in other types of cancers, such as ovarian cancer [12], breast cancer [13], papillary thyroid carcinoma [14], non-small cell lung cancer [15] and hepatocellular carcinoma [16]. Recent studies demonstrated that P 27 represents lower expression in gastric cancer patients compared to healthy volunteers [4,10,14].…”
Section: Introductionmentioning
confidence: 99%